Kontribusi Muhammadiyah dalam Perkembangan Lembaga Keuangan Syariah di Indonesia - Saroni, Slamet; Ote, Oktavianus Ana (Masterpiece: Journal of Islamic Studies and Social Sciences, 2025)
Muhammadiyah, as a community organization with the largest assets in Indonesia, plays a significant role in supporting the development of Islamic finance through the Muhammadiyah Charity (AUM). The Qur'an and Hadith are the main guidelines for Muhammadiyah in carrying out its Charity. The purpose of this study is to provide an overview of Muhammadiyah's contribution to the development of Islamic financial institutions in Indonesia. This research method uses a literature study approach. The results of this study show that Muhammadiyah contributes to the development of Islamic financial institutions in Indonesia. This can be seen from Muhammadiyah's role in distributing its assets to Islamic banks in Indonesia, as well as the use of AUM such as BTM, Insurance, and waqf for channeling funds to the community to improve the development of the Islamic economy and finance in Indonesia. Muhammadiyah's challenges in developing Islamic financial businesses include institutional development, socialization, office networks, improving the quality of human resources, and adding capital to support its sustainability and competitiveness.   Abstrak Muhammadiyah, sebagai organisasi masyarakat dengan aset terbesar di Indonesia, berperan signifikan dalam mendukung perkembangan keuangan syariah melalui Amal Usaha Muhammadiyah (AUM). Al-Qur’an dan Hadist adalah pedoman utama Muhammadiyah dalam menjalankan Amal usahanya. Tujuan Penelitian ini untuk memberikan gambaran kontribusi Muhammadiyah dalam perkembangan lembaga keuangan syariah di Indonesia. Metode penelitian ini menggunakan pendekatan studi literatur. Hasil dari penelitian ini menunjukan Muhammadiyah berkontribusi pada perkembangan lembaga keuangan syariah di Indonesia, Hal itu bisa dilihat peran Muhammadiyah dalam membagi asetnya ke bank – bank syariah di Indonesia, serta pemanfaatan AUM seperti BTM, Asuransi, dan wakaf untuk penyaluran dana kepada masyarakat guna meningkatkan perkembangan ekonomi dan keuangan syariah di Indonesia. Tantangan Muhammadiyah dalam mengembangkan usaha keuangan syariah mencakup pengembangan kelembagaan, sosialisasi, jaringan kantor, peningkatan kualitas SDM, dan penambahan modal untuk mendukung keberlanjutan dan daya saingnya.